Liderazgo predominante en la COAC Cámara de Comercio del Cantón Bolívar (Estudios) - Palacios Zurita, Wladimir Alejandro (2023)
Cooperative unions are organizations of the popular united economy made up by people who voluntarily associate so that they may achieve their common interests. Their management requires democratic participation of the members in management, control and leadership activities, which requires a particular leadership style at all levels of the hierarchical structure, able to understand the social and economic objectives of the members, motivate them and commit to achieving said goals with them. This study analyzed the predominant leadership style in the high directives of the COAC Chamber of Commerce of the Bolivar Canton (Board of Directors 2021-2022) to assess whether it is accord to the management style required for COACs. For this purpose, the methodology involving quadrants of the bi-dimensional model was used, applying a survey made by Blake and Mouton to the members of the board of directors. The results were compared to the leadership styles proposed by Lewin. It was concluded that the high executives of the aforementioned cooperative society tend to veer towards leadership focused on achieving high productivity levels, falling into the profile of an authoritarian leader.